TINJAUAN PENYEBAB MINAT MAHASISWA TERHADAP METODOLOGI PENELITIAN KUALITATIF DAN KUANTITATIF (Sebuah Analisis Perbandingan) - Razie, T. Fachrul; Authar, Tanzilul; Zakie Abdillah (Anatesa : Kajian Pendidikan, Sosial dan Keagamaan, 2024)
Research methods are an integral part of the academic process that leads to a deep understanding of a phenomenon. In the context of higher education, students are often faced with a choice between qualitative and quantitative research methodologies. Student interest in these two approaches can be influenced by various factors, ranging from personal preferences to the demands of certain scientific disciplines. In this article, an in-depth review will be carried out on the causes that influence students' interest in qualitative and quantitative research methodologies. A comparative analysis will discuss the differences between these two approaches as well as factors that may influence students' preferences in choosing their research methodology. This research will use a qualitative approach to collect and analyze data. Data collection was carried out by semi-structured interviews with thirty students to explore their views, experiences and motivations in choosing qualitative or quantitative research methodology. Based on the research results, it was found that the main motivation for students to choose qualitative methodology was the desire to understand social phenomena in depth and contextually. Meanwhile, the main motivation for students to choose qualitative methodology is the desire to understand social phenomena in depth and contextually.